MRI-derived diffusion parameters in the human optic nerve and its surrounding sheath during head-down tilt - Darius A. Gerlach (Nature Portfolio, 2017)
Vision: Microgravity may alter optic nerve and surrounding sheath Changes to the optic nerve and surrounding sheath during microgravity could explain why space flight is harmful to an astronaut’s vision. Darius Gerlach from the German Aerospace Center in Cologne and colleagues studied the tissue architecture of the optic nerve and its surrounding sheath in nine healthy men who experienced head-down tilt, a commonly used ground-based model of weightlessness. Using a neuroimaging technique called diffusion tensor imaging, the researchers documented fluid dynamic changes wrought by the microgravity-like conditions that could be due to alterations in the volume and movement of cerebrospinal fluid within and around the optic nerve. The findings may help explain why many astronauts experience poorer vision after long-duration space flights, although more work is needed to explore the effects of true microgravity on the visual system.